1989
DOI: 10.1093/ajcn/50.4.848
|View full text |Cite
|
Sign up to set email alerts
|

Serum zinc changes due to iron supplementation in teen-age pregnancy

Abstract: Serum zinc and iron concentrations in a group of pregnant teen-agers supplemented with a multivitamin were compared during pregnancy with a group supplemented with a multivitamin containing 18 mg Fe. Serum measurements were at 13 wk of gestational age (prestudy) and during supplementation at 20, 32, and 38 wk, delivery, and 4 and 12 wk postpartum. Hematocrit measurements were used to adjust the measured metal concentrations for the diluting effect of the normal blood-volume increase. The non-Fe-group mean, adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 13 publications
0
26
1
Order By: Relevance
“…There appears to be an intriguing interrelation between copper, zinc and Iron in absorption and utilization. On one-hand supplementation of Iron has been reported to affect bio-availability of zinc and copper in iron deficiency anemia by inter element competition in the bowel, while on the other hand bio-availability of copper and iron is affected by zinc supplementation and the impact is reflected in their blood levels (18,25,26). In view of this it becomes important that the judicious supplementation of micronutrients during pregnancy especially in iron deficiency anemia is essential to maintain their optimum blood levels required for the proper growth of the fetus.…”
Section: Discussionmentioning
confidence: 99%
“…There appears to be an intriguing interrelation between copper, zinc and Iron in absorption and utilization. On one-hand supplementation of Iron has been reported to affect bio-availability of zinc and copper in iron deficiency anemia by inter element competition in the bowel, while on the other hand bio-availability of copper and iron is affected by zinc supplementation and the impact is reflected in their blood levels (18,25,26). In view of this it becomes important that the judicious supplementation of micronutrients during pregnancy especially in iron deficiency anemia is essential to maintain their optimum blood levels required for the proper growth of the fetus.…”
Section: Discussionmentioning
confidence: 99%
“…One of the objectives of an iron supplementation is to reduce the prevalence of anemia (Dawson et al, 1989;Angeles et al, 1993). The de®nition of anemia for the Bolivian children living at 4000 m was based on the cut-off value of 144 g/L de®ned in a previous study conducted by our team on Bolivian children (Berger, 1996), a cut-off value similar to the one proposed by Yip (1993).…”
Section: Discussionmentioning
confidence: 99%
“…Short term iron supplementation can also reduce the prevalence of iron de®ciency anemia in a population (Dawson et al, 1989;Angeles et al, 1993;Schultink et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…One of the main problems with research into Zn metabolism is the lack of suitable and sensitive indices of body Zn levels. Dawson et al (1989) found that Fe supplementation resulted in lower serum Zn concentrations in pregnant teenagers, but since serum or plasma Zn concentrations are not considered to be a good index of body Zn levels, no conclusions can be made regarding the effect of Fe supplements on Zn status per se. However, the results could reflect a redistribution of Zn within the body as a result of taking additional Fe.…”
Section: R O N -Z I N C I N T E R a C T I O N Smentioning
confidence: 99%